Pembangunan Aplikasi Web sebagai Media Edukasi Pernikahan Pasangan Muda menggunakan Metode Prototyping - Egia Rosi Subhiyakto; Mutia Rahmi Pratiwi; Swita Amalia Hapsari (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2022)
Marriage is one phases in life which most adults will experience. Regarding marriage, it has become a government priority, as stated in the national development policy, especially in the 2020-2024 RPJMN. The problem that often arises, especially in young couples, is the lack of knowledge about the ins and outs of marriage, causing former marriage and leading to divorce. In this study, we developed an educational media as a website that the public can access. The system development method that we use is the prototyping method. The choice of this method is because of the intense communication between developers and application users, so that we can improve the application prototypes that are built in the future. There are several channels that we provide in order to provide information about parenting, marriage, family, community, and MendadakTanya which we aim for to ask questions with experts in family health. Based on the results of testing the prototype using the black box testing method, the results got are suitable for all the features in the application. Further research will be carried out on the development, improvement and addition of features based on the results of input and evaluation from application users.